Aptitude Test's Predictive Ability for Academic Success in Psychology Student - Farida Agus Setiawati (Psychological Research and Intervention, 2020)
The developments that occur in psychological measurement have an effect on the development of the quality of the tests used. Differential Aptitude Test (DAT) is a psychological test commonly used to measure a person's aptitude. Aptitude measurement needs to be proven on the success of post-aptitude test studies. Therefore, this study aims to examine: (1) the predictive validity of differential aptitude tests in predicting academic success in the context of psychology study programs, and (2) which subtests are influential in predicting the success of studies in psychology study programs. Data collection was carried out using test techniques and documentation techniques. The research subjects were 148 students majoring in psychology at Yogyakarta State University. The data obtained were then analyzed using multiple linear regression analysis techniques, where the subtest scores on the DAT were treated as predictors and the Grade Point Average scores were treated as the dependent variable. Based on the results of the analysis, it can be concluded that: (1) the DAT test can predict the success of the study in the psychology study program; and (2) the subtest in DAT that has the most influence in predicting the success of the study in the psychology study program is the verbal subtest and the numerical subtest.